Modificação superficial de filmes de poliéster usando plasma a baixa temperatura - Costa, Thércio Henrique de Carvalho (2006)
A polyester film has a vast application field, due some properties that are inherent of this kind of material such as, good mechanical resistance, chemical resistance to acids and bases and low production cost. However, this material has some limitations as low superficial tension, flat surface, low affinity to dyers, and poor adhesion which impede the use of the same ones for some finality as good wettability. Among the existent techniques to increase the superficial tension, plasma as energy source is the more promising technique, because of their versatility and for not polluting the environment. The plasma surface polymeric modification has been used for many researchers, because it does not affect the environment with toxic agents, the alterations remains only at nanometric layers and this technique shows expressive results. Then, due to its good acceptance, polyester films were treated with oxygen plasma varying the treatment time from 10 to 60 min with an increase of 10 min to each subsequent treatment. Also, the samples were treated with a gas mixture (nitrogen + oxygen) varying the percentage of each gas the mixture from 0 to 100%, the treatment time remaining constant to all treatments (10 min). After plasma treatment the samples were characterized by contact angle, surface tension, Raman spectroscopy, Infrared attenuated total reflection (IR-ATR) and atomic force microscopy, with the aim to study the wettability increase of treated polyester films as its variables. In the (O2/N2) plasma treatment of polyester films can be observed an increase of superficial roughness superior to those treated by O2 plasma. By the other hand, the chemical modification through the implantation of polar groups at the surface is obtained more easily using O2 plasma treatment